PENGARUH PENDEKATAN RME TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS IX SMPN 3 PALEMBAYAN - Putri, Jahsy Az-Zahra (Jurnal Edukasi dan Penelitian Matematika, 2023)
Learners must be proficient in solving math. The facts in the field show that students in grade IX of SMPN 3 Palembayan TP 2023/2024 have low abilities in this regard. The Realistic Mathematics Education (RME) learning approach can be a solution. This research analyzes problem solving skills and explains how RME improves these skills compared to the Scientific approach. A static group design was used for this descriptive quasi-experimental study. Math problem solving quizzes and assessments were used. The development of all indicators was inferred using the quiz data. By rejecting H0, the P-value = 0.038 indicated that the RME technique had an impact on problem solving.Keywords – Mathematical Problem Solving, RME, Scientific